Forget me Nat - Scrivan, Maria (New York, NY : Graphix, an imprint of Scholastic, 2020)
"For the first time in her life, Natalie feels confident. Her talents are being recognized, she has supportive friends, and she's spending a ton of time with her crush, Derek! But when Derek tells Natalie that he just wants to be friends, Natalie's self-confidence quickly changes to self-doubt. As she tries to recover from her broken heart, Natalie casts aside her talents and even her friends. With no one to turn to, Natalie will have to pull herself out of this mess on her own"--Amazon.com.
3.3
3-6
3-6
Keywords: Self-esteem -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Middle school students -- Comic books, strips, etc. -- Juvenile fiction; Middle schools -- Comic books, strips, etc. -- Juvenile fiction; Humorous stories; Self-esteem -- Fiction; Friendship -- Fiction; Middle school students -- Fiction; Middle schools -- Fiction; Humorous stories; Cartoons and comics; Self-esteem -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Middle school students -- Comic books, strips, etc. -- Fiction; Middle schools -- Comic, books, strips, etc. -- Fiction; Humorous graphic novels